Ionized gas properties of the extreme starburst galaxy Haro 11 – temperature and metal abundance discrepancies. Issue 2 (26th May 2021) - Menacho, V; Östlin, G; Bik, A; Adamo, A; Bergvall, N; Della Bruna, L; Hayes, M; Melinder, J; Rivera-Thorsen, T E
ABSTRACT: We use high quality VLT/MUSE data to study the kinematics and the ionized gas properties of Haro 11, a well-known starburst merger system and the closest confirmed Lyman continuum leaking galaxy. We present results from integrated line maps, and from maps in three velocity bins comprising the blueshifted, systemic, and redshifted emission. The kinematic analysis reveals complex velocities resulting from the interplay of virial motions and momentum feedback. Star formation happens intensively in three compact knots (knots A, B, and C), but one, knot C, dominates the energy released in supernovae. The halo is characterized by low gas density and extinction, but with large temperature variations, coincident with fast shock regions. Moreover, we find large temperature discrepancies in knot C, when using different temperature-sensitive lines. The relative impact of the knots in the metal enrichment differs. While knot B is strongly enriching its closest surrounding, knot C is likely the main distributor of metals in the halo. In knot A, part of the metal enriched gas seems to escape through low density channels towards the south. We compare the metallicities from two methods and find large discrepancies in knot C, a shocked area, and the highly ionized zones, that we partially attribute to the effect of shocks. This work shows, that traditional relations developed from averaged measurements or simplified methods, fail to probe the diverse conditions of the gas in extreme environments. We need robust relations that include realistic models where several physical processes are simultaneously at work.